Handmade Books : A Step-by-Step Guide to Crafting Your Own Books - Blake, Kathy (London A Bulfinch Press Book, 1997)
A guide to mastering the art of bookmaking. Starting with the easiest types of books to make - scrolls and bound single sheets - the book presents 15 step-by-step projects, culminating in instructions for multi-signature hardcovers. Others projects include albums and address books.
Include Color Illustration and Glossary
Keywords: Bookbinding -- Books